Electrochemical behavior of thermally sprayed stainless steel coatings in 3.4% NaCl solution - Suegama, P. H.; Fugivara, Cecilio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP]; Fernandez, J.; Delgado, J.; Guilemany, J. M. (Elsevier B.V., 2005)
Four types of stainless steel coatings prepared by a high velocity oxy-fuel spraying system (HVOF) were studied. Differences among coated steels were related to the spraying parameters, which influenced the behavior of the samples against the corrosion. The electrochemical behavior of the stainless steel coatings was strongly influenced by porosity, the presence of micro- and macro-cracks, and also of un-melted particles. Once the electrolyte reached the steel substrate via these defects, the galvanic pair formed between the coating and substrate-accelerated corrosion, leading to the depletion of the coating. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: stainless steel coating; electrochemical techniques; HVOF; steel protection; thermal spraying